Comprehensive Analysis of CRIP1 in Patients with Ovarian Cancer, including ceRNA Network, Immune-Infiltration Pattern, and Clinical Benefit. (31st January 2022) - Qi, Bingli; Liu, Shikai; Liu, Dantong; Yao, Hairong; Yan, Ruixue
Abstract : Background . With the development of sequencing technology, an increasing number of biomarkers have been identified in ovarian cancer (OC). However, there have been few comprehensive analyses of CRIP1 in patients with OC. Methods . Logistic regression analysis was conducted to analyze the correlations between clinical characteristics and CRIP1 expression. Kaplan-Meier survival analysis was used to explore the difference in survival in each clinical subgroup. In addition, univariate and multivariate Cox regression analyses were further used to confirm the independent prognostic values of CRIP1 . We further constructed ceRNA network based on the difference analysis. Subsequently, we used the ssGSEA algorithm to excavate the correlation between CRIP1 and tumor-infiltrating immune cells. Moreover, the potential biological functions of CRIP1 were investigated by gene function annotation. Finally, we knocked down CRIP1 gene for preliminary biological function verification in A2780 and SKOV-3 cell lines. Results . The overexpression of CRIP1 was confirmed in The Cancer Genome Atlas (TCGA) cohort, immunohistochemistry, and OC cell lines. CRIP1 overexpression was correlated with the FIGO stage according to a logistic regression analysis that used the median of CRIP1 expression as a categorization of the dependent variable. Survival analysis revealed that CRIP1 was associated with a poor prognosis in most clinical subgroups and acts as an independent prognostic marker in OC patients. In immuno-bioinformatics analysis, CRIP1 is associated to majority of immune cells. This is noteworthy given that we identified that the ceRNA network based on CRIP1 may regulate progression in OC. In addition, gene enrichment analysis suggested CRIP1 may be involved in the JAK-STAT signaling pathway, etc. Finally, we found that knockdown CRIP1 could inhibit the proliferation of OC cells. Conclusion . We provided robust evidences that CRIP1 is an indicator of poor prognosis and a potential target for immunotherapy in patients with OC.